Is fiscal policy dead? - A.T. PEACOCK; G.K. SHAW (PSL Quarterly Review, 2014)
The paper discusses the political and administrative limitations of implementing fiscal policy as a means of achieving economic stability. Present day attitudes towards fiscal intervention are characterised by a general feeling of agnosticism. Not only has confidence waned in the ability of fiscal measures to secure macroeconomic goals, it has been argued that where fiscal changes exert noticeable and significant impacts they may do so in a distinctly perverse and de-stabilising manner. The question now facing policy administrators is whether fiscal policy may usefully be included in the armoury of countercyclical weapons wielded in defence of short-term stabilisation goals. This changed status of fiscal policy has stemmed partly from developments in theoretical economics generally on the one hand, and also from a changed view of the government objective function upon the other.